Advanced AAO Templating of Nanostructured Stimuli‐Responsive Polymers: Hype or Hope?. (3rd October 2019) - Rath, Amrita; Theato, Patrick
Abstract: Nanostructures play a significant role in introducing distinctive functionality to materials. A synergistic combination of nanofabrication techniques with material properties holds great promise in creating smart biomimetic structures. An advanced preparation technique to fabricate complex and sophisticated hierarchical polymeric nanostructure templates via anodized alumina oxide membranes is highlighted. Moreover, nanostructures made of responsive polymers activated by environmental stimuli offer a huge potential in a wide range of applications by enhancing their responsiveness. The current state of research on novel nanostructures fabrication by integrating anodic aluminum oxide with stimuli‐responsive polymers is presented, with an emphasis on the underlying actuation mechanism in terms of application. Furthermore, the potential direction for future research is discussed. Abstract : An advanced fabrication technique to prepare unconventional and hierarchical polymer nanostructures by applying an anodized alumina oxide template is highlighted. It demonstrates a wide range of applications by integrating such a sophisticated structure with responsive polymers activated by environmental stimuli. In‐depth understanding of the actuation mechanism for specific applications is discussed and potential directions for future research are illustrated.